2021
DOI: 10.1038/s41598-021-93241-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and skeletal muscle predictors of impaired cardiorespiratory fitness post-anthracycline chemotherapy for breast cancer

Abstract: This study aimed to characterize peak exercise cardiac function and thigh muscle fatty infiltration and their relationships with VO2peak among anthracycline-treated breast cancer survivors (BCS). BCS who received anthracycline chemotherapy ~ 1 year earlier (n = 16) and matched controls (matched-CON, n = 16) were enrolled. Resting and peak exercise cardiac function, myocardial T1 mapping (marker of fibrosis), and thigh muscle fat infiltration were assessed by magnetic resonance imaging, and VO2peak by cycle tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“… 6 Further, thigh myosteatosis had similar predictive power for low pulmonary VO 2 peak as exercise cardiac function. 7 We also found that greater myosteatosis in the lower leg was associated with decreased O 2 consumption and extraction by the lower leg during submaximal plantarflexion (ie, toe-pointing) exercise. 6 Similarly, while the functional implications are not yet clear, we found that intermuscular fat within the paraspinal (postural) muscles significantly increased within the first 3 months of trastuzumab-containing chemotherapy and persisted to 12 months.…”
Section: Introductionsupporting
confidence: 52%
“… 6 Further, thigh myosteatosis had similar predictive power for low pulmonary VO 2 peak as exercise cardiac function. 7 We also found that greater myosteatosis in the lower leg was associated with decreased O 2 consumption and extraction by the lower leg during submaximal plantarflexion (ie, toe-pointing) exercise. 6 Similarly, while the functional implications are not yet clear, we found that intermuscular fat within the paraspinal (postural) muscles significantly increased within the first 3 months of trastuzumab-containing chemotherapy and persisted to 12 months.…”
Section: Introductionsupporting
confidence: 52%
“…By leveraging primarily cardiac features to predict peak V o 2 , the investigators have focused on the “cardiocentric” contributors to fitness, thereby providing a clear mechanistic link between subclinical cardiac dysfunction and impaired fitness in this population. In contrast, as CRF is determined by multisystem organ health ( 9 ), a focus on cardiac abnormalities may result in a large amount of unexplained variation in peak V o 2 , as observed in this study. Incorporating data from simple exercise studies that can be performed in the physician’s office (eg, exercise treadmill or 6-minute walk tests) may yield models with better predictive performance in future studies.…”
mentioning
confidence: 57%
“…Moreover, among anthracycline-treated early-stage breast cancer survivors, we found that impaired cardiac reserve and thigh muscle fatty infiltration were associated with impaired oxygen extraction, both contributing to reduced V o 2peak . 12 In a secondary analysis of the MANTICORE (Multidisciplinary Approach to Novel Therapies in Cardio-Oncology Research) study, we observed a significant increase in fatty infiltration of skeletal muscle and increased visceral fat without concurrent change in BMI. 13 BMI categories of overweight and obese are considered CVD risk factors, but BMI cannot distinguish body fat percentage or fat location.…”
mentioning
confidence: 79%